Justification of the expanding feed expanding - Zimbrovsky, D. (My University, 2021)
The increase in the efficiency of the livestock industry is largely due to the improvement of existing and development of new production technologies. Among them, great importance is attached to technological methods for the production of complete feed mixtures, balanced in basic nutrients, which meet the physiological needs of animals and ensure a high realization of the genetic potential of their productivity. In the world practice of feed production, there are many methods and technologies for processing grain raw materials in order to increase its nutritional value.
Keywords: feed production; technologies for processing; biologically active substances; vitamin complex; quality of feed; expansion process